A case of Flavonifractor plautii blood stream infection in a severe burn patient and a review of the literature. Issue 3 (4th May 2022) - Costescu Strachinaru, Diana Isabela; Gallez, Jean-Luc; Daras, Sonia; Paridaens, Marie-Sophie; Engel, Harald; François, Pierre-Michel; Rose, Thomas; Vanbrabant, Peter; Soentjens, Patrick
ABSTRACT: Background: Flavonifractor plautii is a strictly anaerobic rod shaped bacterium belonging to the family of Clostridiales . It is a commensal of the human intestinal microbiota which was seldom isolated from clinical samples, therefore clinical data are scarce. To date, only four cases of F. plautii infections were described, all occurring in immunosuppressed patients. Case presentation: We report a case where F. plautii was isolated from the blood culture of a severe burn victim and identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry. Discussion: To the best of our knowledge, this is the first case of F. plautii blood stream infection described in a burn patient.